Alterations of blood immune cells in COVID-19 elderly patients with or without type 2 diabetes - Salva, Maria Susana (2021)
Elderly individuals, especially those with pre-existing conditions like diabetes mellitus (DM), have a high risk for developing severe cases of COVID-19. The aim of this work was to characterize the alterations of blood immune cells (BIC) in patients with symptomatic COVID-19 and confirmed SARS-CoV-2 infection, ≥ 60 years and who needed hospitalization in the Centro de Salud Hospital of Tucuman during the second peak of the pandemic. Blood samples were taken at the time of admission (d0) and five days after (d5) for routine laboratory tests and the characterization of BIC by flow cytometry. Most of the patients were men (70%) aged between 60 and 78 years. The 70% of patients had DM while 50% had arterial hypertension. At d0, all the patients had increased neutrophils and inflammatory markers (C reactive protein and D-dimers) and reduced numbers of lymphocytes, HLA-DRhi monocytes, CD16+CD56+ NK cells, CD3+HLA-DR+CD25+ cells, CD4+ and CD8+ T cells in blood. Patients received a standard treatment for COVID-19 care (O2, corticosteroids and antibiotics). The treatment normalized the levels of BIC (d5) in 30% of patients who were those with no comorbidities. In patients with DM, BIC recovery was variable. In DM patients who required administration of plasma (30%), prolonged O2 therapy (40%) or referral to the intensive care unit (10%) significant reductions of CD16+CD56+, CD3+HLA-DR+CD25+, CD4+ and CD8+ cells were observed between d0 and d5. In line with previous studies, our results shows that absolute counts of major lymphocyte subsets in blood are significantly and substantially decreased during the course of severe COVID-19 disease in elderly patients. These BIC alterations may persist despite clinical care in elderly patients with DM. Further studies are needed to investigate the utility of early lymphocyte subset measurements as prognostic biomarkers of disease severity, mortality, and response to treatment in COVID-19 elderly patients with DM.